Analysis of the influence internal and external factors on the performance of IDXV30 - Tumpal Samosir; Pardomuan Sihombing (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
In this research, authors examine the internal influence of BI7DRR, Inflation, Exchange Rate and JCI and external DJIA, the Fed, HSI and the contribution of factors that influence the performance of Index Value 30 (IDXV30) during the period September 2019 – December 2022. Type of data used is monthly time series data using the saturated sampling technique which is processed using the Eviews 12 application program using the VECM analysis method. The analysis phase is through the Stationarity Test, Optimal Lag Test, VAR Stability Test, Granger Causality Test, Cointegration Test, Impulse Response Function (IRF), and Forecast Error Variance Decomposition (FEVD). The results of the study prove that the Exchange Rate and DJIA together have a negative influence on the performance of the IDXV30 while the HSI and Inflation positively affect the IDXV30's performance. JCI, BI7DRR, FED have a negative influence on the performance of IDXV30. While the contributing factors are the IDXV30 itself while macroeconomics and global stock exchanges do not contribute.